A response to: Almahmoud, O. (2021). Do newborns really don't talk, or are we just not skillful enough to understand them? Journal of Neonatal Nursing. Early view. Issue 6 (December 2021) - Harding, C.; Crossley, S.-L.; Whiting, L.; Petty, J.
Abstract: Neonatal practitioners are increasingly recognising that it is important to be aware of how we can communicate with the infants cared for in neonatal units. It is also essential that there is a clear understanding of what communication and interaction are, beyond responsiveness to infant states when caring for infants and their families. Providing families with tools that will maximise positive everyday speech, language and communication interactions is essential.